2001
DOI: 10.1038/modpathol.3880378
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Calcification of the Airways

Abstract: Airway calcification is usually restricted to the cartilaginous conducting portion of the bronchial tree. Alternatively, calcification of the alveoli is a relatively common consequence of calcium and phosphate imbalance. We wish to report an unusual case in which diffuse calcification of the entire bronchial tree, absent alveolar calcification, was identified in a patient with renal dysfunction. Pathologists should not exclude metastatic calcification when considering the etiology of bronchial calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
1
Order By: Relevance
“…2 These can all arise in the setting of chronic renal insufficiency and secondary or tertiary hyperparathyroidism, which favors the deposition of calcium salts in the viscera. 1,4 Microscopically, calcium deposition occurs in the alveolar epithelial basement membranes, although it can also happen in the alveolar-capillary walls, bronchial walls, and bronchioles. They can be linear or granular, and larger accumulations happen where alveoli open into alveolar ducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 These can all arise in the setting of chronic renal insufficiency and secondary or tertiary hyperparathyroidism, which favors the deposition of calcium salts in the viscera. 1,4 Microscopically, calcium deposition occurs in the alveolar epithelial basement membranes, although it can also happen in the alveolar-capillary walls, bronchial walls, and bronchioles. They can be linear or granular, and larger accumulations happen where alveoli open into alveolar ducts.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is known that peripheral neuropathy is produced in chronic obstructive pulmonary disease and that it is characteristically caused by long-term exposure to cigarette smoke. 4 Furthermore, experimental results suggest that chronic nicotine increases hypersensitivity after peripheral nerve injury. 5 In addition, it has been experimentally demonstrated that repeated myelin degradation and axonal degeneration after injury, which is called Wallerian degeneration, is accompanied by Schwann cell proliferation.…”
Section: A Plausible Neural Origin Through Chronic Tobacco Mucosa Irr...mentioning
confidence: 99%
“…Tracheobronchopathia osteochondroplastica usually presents as cartilaginous spurs or as endobronchial masses that may cause distortion or abnormal narrowing of the airway, and is typically discovered as an incidental finding on chest CT or bronchoscopy. [5][6][7] Only in rare cases does tracheobronchopathia osteochondroplastica cause symptomatic luminal obstruction requiring endobronchial debridement.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, it is important to pay attention for tracheobronchial calcification on preoperative imaging as it may complicate the airway anastomosis during the LTx procedure. Tracheobronchial calcification is an uncommon radiological finding reported to be associated with old age, females, hypercalcemia, and sarcoidosis (32)(33)(34). Extensive calcification of the main bronchi may cause fragmentation of the airway cartilage during manipulation, dissection, or performing the anastomosis.…”
Section: Calcified Airwaymentioning
confidence: 99%